Use of mixed reality for the training of operators of mobile elevating work platforms with the aim of increasing the level of health and safety at work and reducing training costs - Gasparello, Paolo Simone; Facenza, Gabriele; Vanni, Federico; Nicoletti, Alessandro; Piazza, Fabio; Monica, Luigi; Anastasi, Sara; Cristaudo, Alfonso; Bergamasco, Massimo (Frontiers in Virtual Reality, 2022)
The article presents an immersive multisensory simulator developed in a project co-financed by INAIL (the Italian National Institute for Insurance against Accidents at Work) as part of a collaborative research program for the application of innovative technologies and systems to the management of health and safety at work. Specifically, the program provides for the development of simulators for the structuring of skills qualification paths for operators in charge of running and maintaining the most dangerous work equipment. The simulator we present reproduces all the aspects that contribute to a complete driving experience of the simulated machine in an artificial working environment that replicates typical and atypical operations and hazards involved in the use of self-propelled mobile elevating work platforms (MEWPs) with an extendable articulated boom. The simulator has been designed following the analysis of the most critical working routines with aerial work platforms and using physical components of a real MEWP combined with immersive Virtual Reality technologies. The use of Extended Reality technologies to simulate challenging work scenarios makes it possible to train operators by confronting them with very risky situations without any real danger, both in terms of damage to machinery, and above all in terms of user’s safety. The presented simulation system has been designed as a high-TRL prototype to demonstrate the feasibility of developing training programs in the context of occupational safety and health, based on a mixed-reality simulator targeting MEWP operators and verifiers.